If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5 + -3x = -55 Reorder the terms: 5 + -1x + -3x = -55 Combine like terms: -1x + -3x = -4x 5 + -4x = -55 Solving 5 + -4x = -55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = -55 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = -55 + -5 -4x = -55 + -5 Combine like terms: -55 + -5 = -60 -4x = -60 Divide each side by '-4'. x = 15 Simplifying x = 15
| 5x-35=x-13 | | 10x=15x-15 | | 8x-6=5x-12 | | 2(23-x-2y)+2(23-x-7)=20 | | 4(x+3)=3x+3 | | 2(x+2)=3x-4 | | 2v+4=-2(2v+4) | | -6-7(5k-7)=3k-11(1+4k) | | 0=2x^3+8x+1 | | y=392-47.5x | | (-2*-2*-2*-2)-3(6+7)= | | 10=2x+8x | | 2+5r=26 | | 3n+24= | | x+y+2z=23 | | -1+x=x+11 | | x+6=1+2x+8 | | 0.16(y-8)+0.10y=0.18y-0.09(10) | | 11(-7n+4)=-23-11n | | 1.5k+3.5=-4 | | -3x-24=-6x+33 | | 10(1-p)=10(p+9) | | 12u+17y=891 | | 36b-9=18b+3 | | 27-2x=x | | 5+2r=26 | | (3x+2y)2= | | 13xsquared+26x+14=0 | | -12+10x=9x+13 | | -22(x+1)=-11(x+2) | | 9-2g=-5 | | 36b-1=18b+3 |